SPECTROCHEMICAL CHARACTERIZATION OF AN ELECTRON TRANSFER MINIATURIZED PROTEIN SCAFFOLD MIMICS RUBREDOXIN METAL SITE: MOLYBDENUM – MINIATURIZED ELECTRON TRANSFER PROTEIN-SINGLE CHAIN 1 (MO-METPSC1) - Odwan, Rafeef (An-Najah National University, 2024)
Metal atoms are crucial in catalysis and are integral to the structure and function of many enzymes and proteins. A primary goal in protein design is to develop small, stable, and simple peptide scaffolds that can replicate the catalytic activity of complex protein metal centers. These artificial mimics have significant potential in areas such as environmental applications, biotechnology, and fundamental research. In this study, we focused on the Miniaturized Electron Transfer Protein single chain 1 (METPsc1) peptide, reconstituted to mimic a rubredoxin-like metal-binding site with a precise tetrathiolate environment. The reconstitution of the Molybdenum-Miniaturized Electron Transfer Protein single chain 1 (Mo-METPsc1) peptide was achieved using varying peptide-to-metal ratios. It was characterized through multiple spectroscopic techniques, including UV-Vis, Circular Dichroism (CD), and Magnetic Circular Dichroism (MCD) spectroscopy. UV-vis spectroscopy identified two broad absorption bands, with peaks between 310-330 nm and 420-460 nm, indicating successful incorporation of molybdenum into the tetrathiolate environment. CD spectroscopy provided additional confirmation of molybdenum binding, evidenced by a positive band at 394 nm. MCD spectroscopy, which is sensitive to electronic structure and oxidation state, revealed that the molybdenum in the metal-binding site is in the +6 oxidation state (Mo (VI)). Those spectroscopic analyses support molybdenum's successful incorporation and functionality within the peptide scaffold. To further investigate the reduction capabilities of the Mo-METPsc1 complex, reduction studies were conducted using dithionate and dithiothreitol (DTT) as substrates. Spectroscopic analysis following these tests demonstrated the compound's catalytic activity in reducing the dithionate molecule.
التوصيف الطيفي الكيميائي لسقالة بروتين مصغرة لنقل الإلكترون تحاكي موقع معدن الروبريدوكسين: ال موليبدينوم - سلسلة بروتين نقل الإلكترون المصغرة 1 (Mo-METPsc1)